Efeitos de um treinamento multicomponente no controle autonômico cardíaco de idosos pré-frágeis - Farche, Ana Claudia Silva (Universidade Federal de São Carlos, 2020)
Frailty syndrome represents a clinical state of vulnerability to stress, and is characterized by a reduction of capacity to maintain homeostasis. Due to the multidimensionality of Frailty, cardiovascular outcomes have already been related to deficits on autonomic nervous system (ANS) regulation in intermediate stages (prefrailty) on rest. However, the cardiac autonomic control of this population has not been described in the literature, considering the exercise and recovery situations. Once multicomponent physical exercise is described as fundamental in frailty treatment, it is important to assess whether prefrail older adults already presents cardiac autonomic modulation impairments during the exercise and on recovery period, as well as to evaluate the effects of a multicomponent training protocol under them. Thus, this thesis was divided into three studies: The Study I, entitled “Cardiac autonomic responses during the exercise on prefrail older adults: a cross-sectional study”, it was planned to investigate the cardiac autonomic modulation during the six-minute walk test (6MWT); The Study II, entitled “Multicomponent training improve cardiac autonomic modulation responses during the exercise on prefrail older adults: a blinded randomized clinical study”, aimed evaluate the effects of the intervention on cardiac autonomic modulation during the six-minute walk test (6MWT); and the Study III, entitled “Effects of a multicomponent training on heart rate recovery of prefrail older adults: a blinded randomized clinical study”, it was designed to assess the effects of the intervention on heart rate recovery dynamics on prefrail older adults. For this, a multicomponent intervention protocol for prefrail older adults was elaborated and published. Thus, our results showed that prefrail older adults already presents deficits on ANS regulation during and after the exercise. Besides, the multicomponent intervention was able to minimize these deficits during the exercise, but not in the recovery period.
Effects of a multicomponent training on cardiac autonomic control in prefrail older adults
Keywords: Fragilidade; Controle autonômico; Envelhecimento; Exercício físico; Recuperação; Frailty; Autonomic control; Aging; Physical exercise; Recovery; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL